The Emotional Meaning behind Typefaces: Developing Typefaces Bank (TB) for Business and Brand Construction - Adinugroho, Indro (International Journal of Engineering and Technology, 2018)
Typefaces are considered as tiny element yet uncategorized as the primary element in a verbal message. Even though, numerous researches have shown opposite results regarding typefaces. Typefaces are revealed as the element that effects human perception and decision making, especially in business and consumer behavioral circumstances. Typefaces exist as the element that could affect human emotion, the most prominent variable in deciding human behavior. Based on many empirical pieces of evidence, in this study, author gathered approximately 2108 typefaces from three primary sources and evaluated the emotional meaning behind each typeface. Author named these typefaces collection as Typefaces Bank (TB). TB can be valuable for many brand developers and entrepreneurs to construct their brand in public and also deliver impression in business relationships. As an attempt to give emotional meaning to TB, the author applied circumplex model of affect developed by James Russell in 1980, which categorized emotion in two primary aspects, namely valence, and arousal. Self-Assessment Manikin (SAM) is applied to measure valence and arousal degree in each typeface. Result showed that each typeface is categorized in four quadrants produced by the combination between valence and arousal poles.